1998
DOI: 10.1063/1.368915
|View full text |Cite
|
Sign up to set email alerts
|

Electron beam induced changes in the refractive index and film thickness of amorphous AsxS100−x and AsxSe100−x films

Abstract: In this article, electron beam induced changes in the refractive index and film thickness of time relaxed amorphous AsxS100−x (with x=30–45) and AsxSe100−x (with x=40–70) are studied. The largest index change (∼0.08) in AsxS100−x films is found when x=40. The corresponding value (∼0.06) for AsxSe100−x films is met when x=55. The difference in the best compositions is attributed to the different relaxation processes of As–S and As–Se films. Electron beam irradiation causes surface shrinkage of the films. In Asx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…According to the AFM images and appropriate cross-sections, the surface perturbation looks as very small distortions, several nanometres in height, see figure 3(g), curves 3 and 4. Similar behaviour was observed by other investigators earlier [18]. However, SRs are far more prominent in annealed films (figures 3, curves 5 and 6) especially under prolonged e-beam exposure, more than 60 s (see appropriate curves in figures 3(h)).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…According to the AFM images and appropriate cross-sections, the surface perturbation looks as very small distortions, several nanometres in height, see figure 3(g), curves 3 and 4. Similar behaviour was observed by other investigators earlier [18]. However, SRs are far more prominent in annealed films (figures 3, curves 5 and 6) especially under prolonged e-beam exposure, more than 60 s (see appropriate curves in figures 3(h)).…”
Section: Resultssupporting
confidence: 72%
“…There is not much information available about the response of amorphous thin films with different compositions to the e-beam. We have found only the paper devoted to such a response for thin films of As c Se 1−c system mostly for stoichiometric and over-stoichiometric compositions (0.4 c 0.7) [18]. Summarizing, such type of experiments revealed that different kind of surface deformation (ridges or grooves) takes place by e-beam irradiation depending on the composition and the electron current dose.…”
Section: Aq1mentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative explanation to crystallization by surface photo-oxidation of As 40 S 60 rib waveguides, formed in thermally-evaporated As 40 S 60 films, Wang et al (2006) have referred to a type of intrinsic phase separation in As 40 S 60 to explain crystallization of pulsed laser deposited films of As 40 S 60 , and this intrinsic phase separation is suggested to be present even in As 40 S 60 bulk glass itself, according to the ideas of Georgie et al (2003), but these ideas are not universally accepted. As eloquently reviewed by Nordman et al (1998), what is generally accepted is that thermally-evaporated As 40 S 60 films inevitably contain the molecular clusters, composed of both hetero-polar bonds and homo-polar 'wrong' bonds, found in the vapour state itself, and that heat-treating can help to lower the prevalence of the 'wrong bonds' and also densify thermally-evaporated films to achieve more nearly the same refractive index as that of the parent bulk-glass.…”
Section: Discussionmentioning
confidence: 99%
“…3 As an alternative explanation to crystallization by surface photooxidation of As 40 S 60 rib waveguides, formed in thermally evaporated As 40 S 60 films, Wang et al 35 have referred to a type of intrinsic phase separation in As 40 S 60 to explain crystallization of pulsed laser deposited films of As 40 S 60 , and this intrinsic phase separation is suggested to be present even in As 40 S 60 bulk glass itself, according to the ideas of Georgie et al, 36 but these ideas are not universally accepted. As eloquently reviewed by Nordman et al, 37 what is generally accepted is that thermally evaporated As 40 S 60 films inevitably contain molecular clusters, composed of both heteropolar bonds and homopolar "wrong" bonds, found in the vapor state itself, and that heat-treating can help to lower the prevalence of the "wrong bonds" and also densify thermally evaporated films to achieve more nearly the same refractive index as that of the parent bulk glass. From the above studies, it might be concluded that the thermal-evaporation process may be more problematic and that RF-sputtering might lead to more robust glass films.…”
Section: During Manufacturementioning
confidence: 99%